Not An Easy Way Up: A Life History of A Middle Class Filipino Family - Oracion, Enrique G. (Silliman Journal, 2022)
This case study focuses on an emerging middle class 1 Filipino family, its life history, its struggle to break out of the economic marginalities and impoverishment of lower class life, and its attempts to find a niche within the upper class. In my analysis, I situate the middle class along the notions of contradictory class locations and economic marginalities in order to understand its private class struggle for self-improvement. Specifically, the study examines how this family negotiates the two contradictory class positions it occupies, on the one hand, as proletariat, and on the other, as a petty capitalist, and how these positions have accorded it a more comfortable and dignified life at present than when this family was newly formed. Results of the case study show that the economic capital this family accumulated through many years of hard work, perseverance, determination, and frugality has been transformed into cultural capital that the children now enjoy. However, the study also found out that with cultural restrictions legitimizing one's membership in the privileged class of the rich, this family has no prospect of moving beyond their present social position. Additionally, the study also revealed that the ability of the latter generation to reproduce the middle class status they inherit from their parents is largely determined by the personal qualities they had emulated, Therefore, this paper argues that human agency remains the determining factor for social mobility amidst cultural and structural restrictions.